1989
DOI: 10.1021/bi00430a052
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics, binding constant, and activation energy of the 48-kDa protein-rhodopsin complex by extra-metarhodopsin II

Abstract: We have found that the 48-kDa protein (or S-antigen 48k) of the rod photoreceptor enhances the light-induced formation of the photoproduct metarhodopsin II (MII) from prephosphorylated rhodopsin. The effect is analogous to the known enhancement of MII (extra-MII) that results from selective interaction of MII with G-protein. We have determined some parameters of the MII-48k interaction by measuring the extra-MII absorption change induced by the 48-kDa protein. The amplitude saturation yields a dissociation con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
194
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(217 citation statements)
references
References 31 publications
22
194
0
1
Order By: Relevance
“…Interpreted in the context of the crystal structure, this model predicts that stabilizing intramolecular interactions are sequentially broken by an active phosphoreceptor, which allows arrestin to undergo the significant conformational rearrangement necessary for its transition into a high affinity receptor binding state (19,24). In the case of visual arrestin, this prediction was corroborated by extensive structure-based mutagenesis (15,25).…”
Section: Discussionmentioning
confidence: 96%
“…Interpreted in the context of the crystal structure, this model predicts that stabilizing intramolecular interactions are sequentially broken by an active phosphoreceptor, which allows arrestin to undergo the significant conformational rearrangement necessary for its transition into a high affinity receptor binding state (19,24). In the case of visual arrestin, this prediction was corroborated by extensive structure-based mutagenesis (15,25).…”
Section: Discussionmentioning
confidence: 96%
“…The current model for the understanding of the arrestinreceptor interaction mechanism is based on various studies of visual arrestin interaction with rhodopsin (11)(12)(13)(14)(15)(16). Visual arrestin binding with rhodopsin requires GRK-1 phosphorylated residues, and the contact of phosphorylated residues with a cationic region of arrestin switches it into an active conformation, enabling interaction with an exposed binding site on activated rhodopsin.…”
Section: Agonist Binding To Most G Protein-coupled Receptorsmentioning
confidence: 99%
“…1) (4-7). Arrestin-1 was proposed to undergo a conformational rearrangement during the P-Rh* interaction that results in the release of the C-terminal sequence (C tail) (8, 9) but does not involve major secondary structure changes (8,10). Recent site-directed spin labeling (SDSL) studies identified specific parts of arrestin-1 engaged by different functional forms of rhodopsin and provided direct evidence of binding-induced conformational changes (11,12).…”
mentioning
confidence: 99%